Exposing the Elusive Exocyst Structure. Issue 9 (September 2018) - Lepore, Dante M.; Martínez-Núñez, Leonora; Munson, Mary
Abstract : A major challenge for a molecular understanding of membrane trafficking has been the elucidation of high-resolution structures of large, multisubunit tethering complexes that spatially and temporally control intracellular membrane fusion. Exocyst is a large hetero-octameric protein complex proposed to tether secretory vesicles at the plasma membrane to provide quality control of soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-mediated membrane fusion. Breakthroughs in methodologies, including sample preparation, biochemical characterization, fluorescence microscopy, and single-particle cryoelectron microscopy, are providing critical insights into the structure and function of the exocyst. These studies now pose more questions than answers for understanding fundamental functional mechanisms, and they open wide the door for future studies to elucidate interactions with protein and membrane partners, potential conformational changes, and molecular insights into tethering reactions. Highlights: Intracellular trafficking, the movement of protein and lipid cargos between different eukaryotic organelles and to the plasma membrane for secretion, is facilitated by small, membrane-bound vesicles and tubules. SNARE proteins provide the energy for membrane fusion to deliver cargos. Major mechanistic questions remain regarding how cargo-containing vesicles are specifically recognized and how the SNARE proteins are activated for membrane fusion and cargo delivery. Tethers are large coiled-coil dimers or multisubunit protein complexes that interact specifically with the vesicle and target membranes, as well as with associated proteins, including small GTPases, SNARE proteins, and Sec1/Munc18 (SM) proteins. Tethers are also proposed to pull the membranes closer together and activate SNARE proteins for fusion. Elucidation of the function of tethering complexes at the molecular level requires multidisciplinary approaches. These include high-resolution structures, genetics, in vivo functional assays, and in vitro reconstitution experiments. Here, we describe recent progress in determining the structure (both in vitro and in vivo ) of the yeast exocyst complex, which controls fusion of secretory vesicles at the plasma membrane to facilitate cellular growth, signaling, and division.